Segmental Cystic Dilatation of Ureter in Children - Karaman, Abdurrahman; Demircan, Mehmet; Uguralp, Sema; Ceran Ozcan, Canan; Sigirci, Ahmet (Annals of Medical Research, 2021)
None
Keywords: Ureter, Cystic Dilatation of Ureter, Segmental Megaureter, Megaureter, Children